Potential antifungals of natural origin for the treatment of feline sporotrichosis (Research, Society and Development, 2024)
Sporotrichosis, a fungal disease caused by Sporothrix and affecting both humans and felines, is commonly treated with oral Itraconazole for extended periods, however, the increasing resistance to the antifungal resulting from interruptions in treatment has been observed. In this scenario, essential oils and plant extracts emerge as potential therapeutic alternatives more effective compared to existing drugs. The aim of this review is to provide a comprehensive and updated overview of plant oils and extracts against strains of Sporothrix spp., which may contribute in the future to the development of more effective and safer therapies for this important zoonosis. In vitro studies evaluated the fungistatic action by determining the Minimum Inhibitory Concentration (MIC) and the fungicidal action by determining the Minimum Fungicidal Concentration (MFC), the latter including cell viability studies. In vivo studies in animal models generally determined the reduction of disease symptoms and fungal burden, remission of clinical symptoms, and dissemination of the fungus to organs. The analyzed studies indicated that these plant compounds have potential efficacy against the fungus, especially for strains of S. brasiliensis and S. schenckii, however, methodological standardization is necessary for proper comparison of results. Overall, the future use of these natural antifungals in oral or topical formulations may represent a significant advancement in the treatment of feline sporotrichosis, minimizing its complications.